SYNERGITY ANALYSIS on LOCAL INSTITUTIONAL Of VILLAGE FUND MANAGEMENT (Case Study on Jungsemi Village, Kangkung District, Kendal Regency, Central Java Province) - Noor, Munawar (Advances in Social Sciences Research Journal, 2020)
The problem of this study was how is the synergy of local institutions to manage village funds and what there were the inhibiting / supporting factors for managing village funds for village development. This study was to describe and analyze the synergy of local institutions in the management of village funds and to describe and analyze obstacles and support factors in managing village funds for development. This research used a phenomenological qualitative approach, because the qualitative approach has characteristics, including: having an actual sett, and the researcher was the key instrument. The data was usually descriptive, emphasizes the process, the data analysis was inductive, and the meaning of each event was essential attention. Data analysis used an interactive model, namely the analysis technique which is an integral cycle between data collection, data reduction, data display and conclusion. The synergy of village institutions in Jungsemi Village was well developed because it involved various existing institutions and operated in various sectors of the village funds management, transparency or openness must be built with the community and with existing village institutions